2015
DOI: 10.1016/j.trc.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Personalised assistance for fuel-efficient driving

Abstract: a b s t r a c tRecent advances in technology are changing the way how everyday activities are performed. Technologies in the traffic domain provide diverse instruments of gathering and analysing data for more fuel-efficient, safe, and convenient travelling for both drivers and passengers. In this article, we propose a reference architecture for a context-aware driving assistant system. Moreover, we exemplify this architecture with a real prototype of a driving assistance system called Driving coach. This proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 30 publications
0
72
0
Order By: Relevance
“…A context‐aware driving assist system was prototyped by Gilman et al . Zhao et al . developed eco‐driving feedback system and reported idling for a long time as one of the contributing factors for non‐eco‐driving.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A context‐aware driving assist system was prototyped by Gilman et al . Zhao et al . developed eco‐driving feedback system and reported idling for a long time as one of the contributing factors for non‐eco‐driving.…”
Section: Related Literaturementioning
confidence: 99%
“…Jamson et al[46] used a driving simulator to investigate the rate of learning of eco-driving, where steady driving is important for fuel-efficient driving. A context-aware driving assist system was prototyped by Gilman et al [47] Zhao et al[48] developed eco-driving feedback system and reported idling for a long time as one of the contributing factors for non-eco-driving. Car navigation system is also evolving as a driver assist system for reduction in fuel consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many phone applications already provide their users with information about, for instance, the travel time to home at the end of a working day, route conditions, or traffic jams. Secondly, predictions may help to save energy on the societal level, for instance, by fuel savings via carpooling or real time route optimisation . Thirdly, predictions may be used for providing personalized content, for instance, via location‐based social networks .…”
Section: Introductionmentioning
confidence: 99%
“…These systems have evolved over time and some exploit the recent advances in CV technology [20,22,23]. Some recent works on driver assistant systems that focus on vehicle fuel economy are available in [24][25][26][27]. Authors [24] have provided optimal velocity and acceleration information to the driver by minimizing an approximate fuel consumption model.…”
Section: Introductionmentioning
confidence: 99%